2007
DOI: 10.1345/aph.1k068
|View full text |Cite
|
Sign up to set email alerts
|

Self-Medication Practices with Antibiotics and Antimalarials Among Sudanese Undergraduate University Students

Abstract: The prevalence of self-medication with antibiotics/antimalarials among undergraduate university students in Khartoum State is high. Our findings highlight the need for planning interventions to promote the judicious use of antibiotics/antimicrobials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
101
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(123 citation statements)
references
References 11 publications
(1 reference statement)
18
101
4
Order By: Relevance
“…In concordance to the results our study, students of health care professionals also reported a high prevalence non prescription drugs usage (Banerjee and Bhadury, 2012;Aditya and Rattan, 2013). The rate of use of antibiotics among the students of health care in different countries were found to be 43.2% in Nigeria (Ehigiator et al, 2013), 47.8% in Southern China (Pan et al, 2012), 79.5% in Sudan (Awad and Eltayeb, 2007) and 48% in Iran (Sarahroodi et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In concordance to the results our study, students of health care professionals also reported a high prevalence non prescription drugs usage (Banerjee and Bhadury, 2012;Aditya and Rattan, 2013). The rate of use of antibiotics among the students of health care in different countries were found to be 43.2% in Nigeria (Ehigiator et al, 2013), 47.8% in Southern China (Pan et al, 2012), 79.5% in Sudan (Awad and Eltayeb, 2007) and 48% in Iran (Sarahroodi et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Written informed consent was taken from all the students. The questionnaire was chosen from previous studies and modified according to the local needs (Awad and Eltayeb, 2007;Kumar et al, 2013). The questionnaire had questions related to demographic information of the participants, name of the antibiotics, indication for use, the information source about the antibiotic, their dose, reasons for self administration and idea about self medication etc.…”
Section: Methodsmentioning
confidence: 99%
“…This could be attributed to the mental state of the students as they think that they are aware of their symptoms and what are the diagnosis and the treatment and this behavior has risks, because wrong or inadequate information expose the subjects to potential health risks. 22 That most frequent side effects was nausea and vomiting 47 (9.3%) which could be due to the sensitivity of chemical component of the medications especially opioids, and also this is followed by decrease in appetite 22 (4.3%), drowsiness 16 (3.2%), and dizziness 13 (2.6%). These side effects depend on age, gender, dose, genetic differences and interaction with other drugs.…”
Section: Discussionmentioning
confidence: 99%
“…117 Many studies have been done to assess the prevalence and practices of self-medication. There has been variation in the measures of self-medication practices as depicted by survey questionnaires from various studies.…”
Section: Discussionmentioning
confidence: 99%